Implementasi dan Evaluasi REST API dalam Integrasi Sistem Lintas Platform - Olivia, Melvina (Jurnal Komputer, 2025)
In today's digital era, online games such as Minecraft are rapidly growing as part of the entertainment industry. Arknesia Entertainment Network developed an independent Minecraft server called Reforged World to improve users' gaming experience. However, there are challenges in integrating server data efficiently. This research aims to develop a RESTful API that integrates with the backend using Express.js, the website frontend using Next.js, and the mobile application using Expo. This RESTful API allows real-time management of server status data, player information, and game statistics. The results show that the RESTful API is able to improve service quality and provide a better user experience. Full documentation is provided to make it easier for other developers to implement and further develop the API.